Blockade of ErbB-2 nuclear function induces the interferon signaling pathway in breast cancer models resistant to Trastuzumab - Elizalde, Patricia Virginia (2022)
Despite clinical efficiency of therapies targeting cell-surface receptor ErbB-2, resistance tosuch drugs is a major issue in breast cancer (BC). ErbB-2 triggers oncogenic signaling when ismembrane-bound, but it also migrates to the nucleus (NErbB-2) where it acts as atranscription regulator.